Production of mealworms for human consumption in Finland: a preliminary life cycle assessment - Joensuu, Katri; Silvenius, Frans (Wageningen Academic Publishers, 2017)
Interest in insect production for human consumption is growing in many European countries, including Finland. One of the main justifications for insect-based food products is their lower environmental burden compared to traditional livestock products; another is the need for new protein sources for animal feed and human consumption. In this study, we investigated the global warming potential (GWP) of the potential future industrial scale mealworm production in Finland, using existing data on input needs of mealworm production in the Netherlands and previous life cycle assessment studies of Finnish feedstocks and energy sources. We compared three scenarios, of which one was based on feeding with a commercial feeding mixture, the second on feeding with food industry by-products and the third on the use of low-emission energy sources in combination with feeding with food industry by-products. In all three scenarios, feed crop production and direct heating energy were responsible for at least 95% of the total GWP. Especially the use of low-emission energy sources appears to have potential in reducing the greenhouse gas emissions of insect production.
Keywords: kasvihuonekaasupäästöt; hyönteiset; kestävä tuotanto; greenhouse gases; insects as food; sustainability